Dyella tabacisoli sp. nov., a bacterium isolated from an arable soil sample of Nicotiana tabacum L. Issue 11 (29th November 2018) - Li, Qing-Qing; Chen, Xing; Zhou, Xing-Kui; Dong, Li-Min; Xiao, Min; Fang, Bao-Zhu; Li, Wen-Jun; Duan, Yan-Qing
Abstract : A Gram-stain-negative, aerobic, non-motile and rod-shaped bacterium, designated strain L4-6 T, was isolated from an arable soil sample of tobacco in Huize, south-western China and subjected to polyphasic taxonomic characterization. The cells showed oxidase-positive and catalase-positive reactions. Growth occurred at 20–35 °C, at pH 5.0–8.0 and with 0–2 % (w/v) NaCl, optimally at 30 °C, pH 6.0–7.0 and 0–1 % (w/v) NaCl. The major respiratory lipoquinone was ubiquinone-8. The predominant cellular fatty acids (>10.0 %) were identified as summed feature 9 (iso-C17 : 1 ω9 c or C16 : 0 10-methyl), iso-C15 : 0 and iso-C17 : 0 . The polar lipid profile contained diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, two unidentified phospholipids, two unidentified aminophospholipids and five unidentified aminolipids. The genomic DNA G+C content was 60.8 mol%. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain L4-6 T should be affiliated to the genus Dyella and formed a clade with the most closely related organism Dyella soli JS12-10 T . 16S rRNA gene sequences similarity analysis showed that strain L4-6 T was mostly closely related to D. soli JS12-10 T (98.73 %) and Dyella lipolytica DHOB07 T (98.02 %). DNA–DNA hybridization data indicated that strain L4-6 T represented a novel genomic species belonging to the genus Dyella . The polyphasic taxonomic characteristics indicated that the strain L4-6 T represents a novel species of the genus Dyella, for which the name Dyella tabacisoli sp. nov. (type strain L4-6 T =CGMCC 1.16273 T =KCTC 62035 T ) is proposed.